2021
DOI: 10.1017/jfm.2021.639
|View full text |Cite
|
Sign up to set email alerts
|

Effects of charge relaxation on the electrohydrodynamic breakup of leaky-dielectric jets

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 54 publications
(162 reference statements)
1
8
0
Order By: Relevance
“…• The electric field does not affect the thinning rate asymptotically close to the pinching point, even though the polarization stress may diverge in that limit. A similar conclusion was obtained for both perfect 15 and non-perfect 16,21 conductors under a radial electric field. In these cases, the asymptotic self-similar solution becomes that of the non-electrified case.…”
Section: Articlesupporting
confidence: 80%
See 1 more Smart Citation
“…• The electric field does not affect the thinning rate asymptotically close to the pinching point, even though the polarization stress may diverge in that limit. A similar conclusion was obtained for both perfect 15 and non-perfect 16,21 conductors under a radial electric field. In these cases, the asymptotic self-similar solution becomes that of the non-electrified case.…”
Section: Articlesupporting
confidence: 80%
“…The tangential electrostatic force also plays a key role in the formation of quasi-spike structures during the breakup of viscoelastic electrically charged jets. 19 Lakdawala et al 20 showed that the local dynamics of a jet in a radial electric field might be altered when the conduction is weak, while Nie et al 21 have numerically shown that charge relaxation does not generally affect the self-similar dynamics at pinch-off of a leaky-dielectric jet.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of ink rheological and elec-trical properties and technological parameters on the cone jets/droplets morphology, fracture mode, and deposition behaviors were studied. As shown in Figure 3 [31][32][33][34][35][36], both qualitative and quantitative results were obtained. For example, the vibration model of the Taylor cone meniscus was developed, and the oscillation characteristics including frequency and mode were calculated [32].…”
Section: Electrohydrodynamic Direct-writing Technologymentioning
confidence: 81%
“…As shown in Figure 3(a), different from traditional "extrusion" inkjet printing technologies such as piezoelectric and thermal bubbles methods, electrohydrodynamic (EHD) jet [32][33][34], Copyright@2021, AIP; Copyright@2019, Elsevier; Copyright@2021, Cambridge University Press. (c) Novel technologies (Mechano-electrospinning, reprinted with permission from ref.…”
Section: Electrohydrodynamic Direct-writing Technologymentioning
confidence: 99%
“…The leaky-dielectric model and ALE technique have proven to be extremely applicable for simulating electrohydrodynamic problems, such as pinching of charged jets (Nie et al. 2021), tip streaming and emission of charged drops (Collins et al. 2008; Wagoner et al.…”
Section: Introductionmentioning
confidence: 99%